Newer insights of H1N1: Swine Flu Virus - Tiwari, Ritu; Verma, Shivam; Verma, Narsingh; Singh, Shraddha; Verma, Ajay; Mittal, Anupam; Haque, Shiraja; Kumar, Toyaj (Indian Journal of Community Health, 2024)
Swine flu, caused by the H1N1 influenza virus, is a subtype of influenza A that affects both the upper and lower respiratory tracts. It is primarily found in pigs and can be transmitted to humans through genetic variations in the virus. The 1918 Spanish flu pandemic resulted in the deaths of 50 to 100 million individuals. In 2009, the pandemic affected 178 countries, resulting in an estimated 43 to 89 million cases and 1799 deaths. The pathophysiology of H1N1 involves inflammation of the respiratory tract, with an incubation period of 1 to 4 days and a contagious period lasting 5 to 7 days. The signs and symptoms of swine flu include cough, sore throat, fever, myalgia, congestion, headache, rhinorrhoea, dizziness, sneezing, loss of appetite, fatigue, abdominal pain, shortness of breath, and in rare cases, vomiting and diarrhoea. The most common cause of death is respiratory failure, and neurological symptoms can occur due to high fever. To diagnose swine flu, various tests such as haematological, biochemical, and microbiological tests are conducted, including the collection of nasal or oral swabs for reverse transcriptase polymerase chain reaction (RT-PCR). Prevention and control measures include managing swine flu in pigs through herd management, hygiene practices, and vaccination. Treatment options vary based on the severity of the case. Mild to moderate cases can be managed with rest, antipyretics, NSAIDs, antihistamines, and oral rehydration therapy. Severe cases may require intravenous hydration, antibiotics for bacterial infections, antiviral therapy, and respiratory support.